2008
DOI: 10.1007/s11606-008-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality Monitoring of Physicians: Linking Patients’ Experiences of Care to Clinical Quality and Outcomes

Abstract: BACKGROUND: Physicians are increasingly asked to improve the delivery of clinical services and patient experiences of care. OBJECTIVE:We evaluated the association between clinical performance and patient experiences in a statewide sample of physician practice sites and a sample of physicians within a large physician group. DESIGN, SETTING, PARTICIPANTS:We separately identified 373 practice sites and 119 individual primary care physicians in Massachusetts. MEASUREMENTS: Using Health Plan Employer Dataand Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 32 publications
3
109
0
1
Order By: Relevance
“…[13][14][15][16][17] For example, patients hospitalized for acute myocardial infarction (AMI) who reported more problems with care had poorer outcomes both one month and twelve months after discharge, although these effects were mediated for patients with subsequently positive outpatient care experiences. 18 Furthermore, patient experience has a strong relationship to patients' adherence to medication and other care regimens.…”
Section: Why Is It Important To Measure Patient Experience?mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] For example, patients hospitalized for acute myocardial infarction (AMI) who reported more problems with care had poorer outcomes both one month and twelve months after discharge, although these effects were mediated for patients with subsequently positive outpatient care experiences. 18 Furthermore, patient experience has a strong relationship to patients' adherence to medication and other care regimens.…”
Section: Why Is It Important To Measure Patient Experience?mentioning
confidence: 99%
“…37,13 Patients' reports of interactions with the health care system can reveal system problems that affect quality and efficiency along with patient experience.…”
Section: -36mentioning
confidence: 99%
“…This is consistent with previous evidence that patient ratings of interpersonal care may not corre- spond to the technical quality of care. [37][38][39][40] Patient reports of discrimination could still be an indicator for other problems during the medical encounter not examined, such as decreased patient trust, which can influence health outcomes through separate pathways and has been shown to be especially important for patients with diabetes. 41 Patients with diabetes and other chronic conditions are typically much more dependent on their healthcare than other patients, and thus the quality of the patient-provider relationship is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that "clinical quality and patient experience are distinct but related domains that require separate measures and improvement initiatives." 19 Kerse and colleagues studied adults being cared for in primary care practices in New Zealand. Patients completed a waiting room survey about attributes of their relationship with their PCP before a visit.…”
Section: Discussionmentioning
confidence: 99%